TINJAUAN HISTORIS SEKALA BEKHAK SEBAGAI MUASAL KEBERADAAN KERATUAN ADAT LAMPUNG - Okta Viyanti Subing; Maskun Maskun; Muhammad Basri (FKIP UNIVERSITAS LAMPUNG, 2013)
The purpose of this study was to determine the origin of the existence of Sekala Bekhak as Lampung Coastal Indigenous Keratuan. The method used in this study is due to the historical method of research that takes an object of the past in general using the historical method. Data collection techniques using library research techniques and documentation techniques, while the data analysis techniques using qualitative data techniques. Results of this study showed that the Sekala Bekhak is a large ancient peradaban. History of the existence of Mr. Sekala Bekhak Paksi closely associated with the founding of Highways or Latin culture both in the area of West Lampung and in other areas in the province of Lampung. In addition, in Sekala Bekhak Takit Pesagi ago, Kedatuan or Indigenous Keratuan has a characteristic rather than the formation of the township itself is taking every different direction. Tujuan dari penelitian ini adalah untuk mengetahui proses Sekala Bekhak sebagai muasal keberadaan Keratuan Adat Lampung Pesisir. Metode yang digunakan dalam penelitian ini adalah metode historis karena penelitian ini mengambil obyek masa lampau. Tekhnik pengumpulan data menggunakan tekhnik studi kepustakaan dan dokumentasi. Tekhnik analisis datanya menggunakan tekhnik data kualitatif. Dari penelitian ini diperoleh hasil bahwa Sekala Bekhak merupakan sebuah Peradaban kuno. Sejarah berdirinya keberadaan paksi Pak Sekala Bekhak erat kaitannya dengan berdirinya marga atau budaya lain di Lampung Barat Takit Pesagi. Terdapat perkampungan atau tiyuh yang masing-masing di dirikan oleh kedatuan atau Keratuan yang mempunyai cirri khas dari setiap arah yang berbeda. Kata kunci: keberadaan, keratuan lampung, sekala bekhak